Lysophosphatidic Acid Triggers Apoptosis in HeLa Cells through the Upregulation of Tumor Necrosis Factor Receptor Superfamily Member 21 - Yunzhou Dong; Yong Wu; Mei-Zhen Cui; Xuemin Xu (Mediators of Inflammation)
Lysophosphatidic acid (LPA), a naturally occurring bioactive phospholipid, activates G protein-coupled receptors (GPCRs), leading to regulation of diverse cellular events including cell survival and apoptosis. Despite extensive studies of the signaling pathways that mediate LPA-regulated cell growth and survival, the mechanisms underlying the apoptotic effect of LPA remain largely unclear. In this study, we investigated this issue in HeLa cells. Our data demonstrate that LPA induces apoptosis in HeLa cells at pathologic concentrations with a concomitant upregulation of the expression of TNFRSF21 (tumor necrosis factor receptor superfamily member 21), also known as death receptor number 6 (DR6) involved in inflammation. Moreover, treatment of cells with LPA receptor (LPAR) antagonist abolished the DR6 upregulation by LPA. LPA-induced DR6 expression was also abrogated by pertussis toxin (PTX), an inhibitor of GPCRs, and by inhibitors of PI3K, PKC, MEK, and ERK. Intriguingly, LPA-induced DR6 expression was specifically blocked by dominant-negative form of PKCδ (PKCδ-DN). LPA-induced DR6 expression was also dramatically inhibited by knockdown of ERK or CREB. These results suggest that activation of the MEK/ERK pathway and the transcription factor CREB mediate LPA-induced DR6 expression. More interestingly, knockdown of DR6 using siRNA approach remarkably attenuated LPA-induced apoptosis. In conclusion, our results suggest that LPA-induced apoptosis in HeLa cells is mediated by the upregulation of DR6 expression.